EFFECT OF CULTURAL CONDITION ON EVALUATION OF HEPATOPROTECTIVE ACTIVITY OF METHANOLIC BARK EXTRACT OF ANOGEISSUS LATIFOLIA ON ETHANOL-INDUCED HEPATOTOXICITY - Bisht, Prateek; S, Chandrashekhara; Das, Kuntal; Tribedi, Sourav (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Geographical location has a great importance on phytoconstituents content in plants. The present study was aimed to understand the impact of soil nature of geographical zone on evaluation of hepatoprotective activity Anogeissus latifolia (AL), (family: Combretaceae) methanolic bark extract on ethanol-induced hepatotoxicity in Wistar rats. Methods: Soil sample was collected and analyzed for various physicochemical properties. Atomic absorption spectrophotometer was used for determination of heavy metals present in soil sample. Thereafter, liver damage was produced by ethanol (3.76 g/kg p.o). The plant extract was administered orally for 25 days. At the end of the study, the biochemical parameters were investigated. Silymarin was used as a standard. Furthermore, histopathology was carried out and characterized by severe vacuolar, cytoplasmic degeneration, and hepatic necrosis. Finally, the impact of soil parameters is correlated with the evaluated study. Results: Analyzed soil sample showed pH is acidic (pH=5.48) and presence of higher amount of iron (Fe), copper (Cu), and zinc (Zn) (77.37 mg/kg, 10.87 mg/kg, and 19.26 mg/kg, respectively) whereas other metals such as nickel, chromium, cadmium, and lead are present in less content. Thereafter, treatment of animals with methanolic extract of AL bark significantly (p<0.05) decrease the levels of serum glutamic oxaloacetic transaminase in serum which is an indicative of hepatoprotective activity. Also brought down the level of serum glutamic pyruvic transaminase significantly (p<0.05 in 200 mg/kg b.w. and 400 mg/kg b.w. doses, respectively). Various parameters physical parameters, cholesterol level, and total protein were estimated. Histopathology studies and triglycerides also were indicative of hepatoprotective property. Conclusion: Finally, the results concluded that the presence of higher amount of Fe and Zn helps to get the significant results of the present investigation which has great impact on liver protection and the selected plant extract showed dose-dependent significant hepatoprotective effect against ethanol-induced hepatotoxicity in Wistar rats.